Pengaruh Promosi, Citra Merek, Dan Desain Produk Terhadap Keputusan Pembelian Konsumen Pada E-Commerce Shopee Di Kota Batam - Siti Khaviva Consina; David Humala Sitorus (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
This research aims to identify the influence of promotions, brand image and product design on consumer purchasing decisions on Shopee e-commerce in Batam City. This type of research uses a quantitative approach. The population consists of buyers from e-commerce Shopee whose exact number cannot be known. The research sample can use the Jacob Cohen formula with a purposive sampling technique which produces 204 respondents. The collected data was analyzed using multiple regression analysis. The data analysis method uses data quality testing, classical assumption testing, influence testing and hypothesis testing. The findings from multiple linear regression analysis are that promotions can increase purchasing decisions by 34.5%. Brand image can increase purchasing decisions by 40.4%. Product design can increase purchasing decisions by 47.0%. The findings from the analysis of the coefficient of determination (R2) are that promotion, brand image and product design can reach 53.3% in explaining purchasing decisions on Shopee e-commerce in Batam City. The results of the research using the t test and f test show that promotion, brand image and product design partially and simultaneously have a positive and significant influence on consumer purchasing decisions on Shopee e-commerce in Batam City.